MENDIDIK ANAK DENGAN CINTA DAN BIJAK: PENGUATAN PERAN ORANG TUA DALAM PENGASUHAN ANAK USIA DINI DI PAUD RAUDLATUL ISLAMIYAH - Kholifah, Siti; Ahmad, Nursaidah; Suedah, Suedah; Safitri, Eka; Ulfah, Ulfah; Aminah, Siti; Umamah, Umamah; Khulduniah, Khulduniah; Yuliah, Elah (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
The parenting activity with the theme "Educating Children with Love and Wisdom" aims to provide parents with an understanding of the importance of balancing positive discipline and affection in early childhood parenting. This activity was held at PAUD Raudotul Islamiah, with Siti Kholifah, M.Pd, a lecturer and early childhood education practitioner, as the resource person. The event included a presentation on the concept of positive discipline based on love, followed by an interactive discussion and a question-and-answer session addressing parenting challenges. The results of this activity show that parents feel more confident in facing parenting challenges and understand the importance of good communication, setting clear boundaries, and applying wise discipline. Furthermore, parents gain practical skills that can be directly applied at home to create a harmonious family environment that supports the optimal growth and development of children. This activity is also expected to serve as an initial step in strengthening the emotional bond between parents and children and in positively shaping children's character.